2019
DOI: 10.2478/prolas-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Tests in Addition to the Alvarado Score in the Management of Acute Appendicitis in School-Age Children

Abstract: The aim of the study was to determine whether the Alvarado score (AS) together with laboratory tests could be used to distinguish patients with acute appendicitis (AA) from acute mesenteric lymphadenitis (AML). Fifty-seven patients (7–18 years) with suspected AA were included in the prospective study (October 2010 – October 2013). Thirty-one patients underwent surgery for AA and 26 were not treated surgically and were diagnosed AML on ultrasonography. AS, white blood cell count (WBC), C – reactive protein (CRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…He et al performed autopsies on patients who died of SARS, and the pathological results showed that in ACE2-expressing cells, monocyte chemokine-1 (MCP-1), tumour growth factor-β1 (TGF-β1), tumour necrosis factor-α (TNF-α), interleukin (IL)-1β and IL-6, were highly expressed [ 21 ]. Referencing our previous study, serum MCP-1 and IL-6 were significantly increased in children with acute complicated appendicitis [ 22 ]. This also could explain the appendiceal rupture within 24 h of disease onset for Patient Nos.…”
Section: Discussionsupporting
confidence: 64%
“…He et al performed autopsies on patients who died of SARS, and the pathological results showed that in ACE2-expressing cells, monocyte chemokine-1 (MCP-1), tumour growth factor-β1 (TGF-β1), tumour necrosis factor-α (TNF-α), interleukin (IL)-1β and IL-6, were highly expressed [ 21 ]. Referencing our previous study, serum MCP-1 and IL-6 were significantly increased in children with acute complicated appendicitis [ 22 ]. This also could explain the appendiceal rupture within 24 h of disease onset for Patient Nos.…”
Section: Discussionsupporting
confidence: 64%
“…The clinical and laboratory criteria served as thresholds for a patient's inclusion into one of the groups (internal hospital document REK-052/01 from 2017). The criteria were based on the previous studies (Zviedre et al, 2019;Taurina et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…During the study period of 2014 to 2015, the Alvarado score alone was used to separate AnA and AcA cases, but the results showed that the diagnosis and treatment should be im- proved and standardised. It was decided to create a diagnostic and treatment algorithm for use in the ED as well as in the paediatric surgery clinic (Zviedre et al. 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations